Some converts, neither decidedly critical nor only spiritualist: Brief balance of a recent diagnosis on the social impact of the new churches (Peru 1995-2000) - Motte, Dominique (2005)
Analysis of the presence of new faiths in Peru throughout the second half of the 20th century.